Trans-catheter ovarian vein coiling in management of symptomatic females having chronic pelvic congestion - Yasser I. Abd Elkhalek; Ahmed Mohamed Mohamed Fahmy Bassiouny (The Egyptian Journal of Radiology and Nuclear Medicine, 2018)
Objectives: To assess the technical success and short term clinical efficacy of trans-catheter ovarian vein coiling in the treatment of symptomatic pelvic congestion syndrome in women. Methods: This study included 10 female patients having pelvic venous congestion treated by coiling and were followed up for 3 months between February 2016 and April 2017 at Ain Shams University hospital, Cairo, Egypt. Symptomatology of pelvic congestion syndrome that was documented either by transvaginal Doppler and/or by MRI with no response to conservative treatment. Results: Symptoms successfully disappeared in 8 patients out of 10. Partial relief of symptoms in one patient that was then disappeared after another session. Only one patient showed no improvement. Conclusion: Our study demonstrates high efficacy of ovarian vein coiling as a new technique in the treatment of symptomatic female patients with pelvic congestion syndrome. Keywords: Pelvic congestion, Coiling